CIRUGÍA ENDOSCÓPICA GINECOLÓGICA: EXPERIENCIA DE 8 AÑOS - Jaime Zarhi T.; Juan M Toso L.; Juan Cifuentes S.; Fernando Vacca G.; Patricio Stuardo A. (Permanyer, 2004)
Se presenta la experiencia de 1046 cirugías laparoscópicas ginecológica del Servicio de Obstetricia y Ginecología del Hospital El Pino, desde julio de 1995 a diciembre de 2003. El 40,5% correspondieron a esterilizaciones tubarias, nivel de complejidad tipo 1 y las restantes a niveles de complejidad tipo 2 y 3. Se reportan los resultados y las complicaciones mayores We report our experience in gynecologic laparoscopic surgery at the Department of Obstetric and Gynecologic of El Pino Public Hospital, since july 1995 to december 2003, were we performed 1046 procedures, which 40.5% were tubal sterilization complexity level 1 and the remaining procedures were level 2 or 3. We present the results and mayor complication of this series